ISSUES OF FORMING FRIENDLY RELATIONS IN A GROUP OF CHILDREN IN THE PREPARATORY GROUP OF PRESCHOOL EDUCATION - Kuranova Ismigul Kholmurod kizi (American Journals Publishing, 2025)
This article provides methodological guidelines and recommendations for the effective use of Abdullah Avloniy's works in fostering friendships among children in the preparatory group. The educational value of stories, fairy tales, and parables, which serve as examples of the teacher's creativity, is examined.
Keywords: Friendships, textbooks “First Teacher”, “Second Teacher” and “Turkish Gulistan, or Morality”.